Behaviour of stainless and high strength steel bolt assemblies at elevated temperatures — A review. (May 2020) - Shaheen, Mohamed A.; Foster, Andrew S.J.; Cunningham, Lee S.; Afshan, Sheida
Abstract: This study documents important aspects of bolt assembly performance in structural steel connections at elevated temperatures that have not been the subject of detailed investigation to date. The codified strength reduction factors listed in the European and US standards are evaluated against experimental results obtained from the literature. It is concluded that the codified reduction factors should be updated as they are in many cases found to be non-conservative, particularly in the high temperature ranges. The effect of fire on the microstructure of steel bolts is also discussed, providing an insight into the roles that phase transformation and metallurgical failure play in the performance of high strength and stainless steel bolt assemblies at elevated temperatures. The study concludes by proposing a new reduction factor equation, based upon experimental results found in the literature. Highlights: Documents important aspects of bolt assembly performance in structural steel connections at elevated temperatures. Identifies areas were more conservatism should be introduced into codes of practice. Proposed an updated reduction factor equation based upon a detailed and critical review of the literature and available data.